Growth and andrographolide content of andrographis paniculata grown on different growing media and media water status - Muslianie Md Isa (School of Bioprocess Engineering, University Malaysia Perlis, 2015)
This study is aims to investigate the effect of different growing media and media water status on the growth and bioactive compound (andrographolide) content of A. paniculata. An experiment was conducted at the greenhouse Institute of Sustainable Agrotechnology (INSAT), Universiti Malaysia Perlis (UniMAP) during April 2012 to February 2013. The experiment was laid out in randomized complete block design (RCBD) of two factors consisting of 9 treatments with 3 replications. Each replication consisted of 24 plants. Three different growing media were applied, namely compost, topsoil and sand. The growing media were combined in different ratios (1:2:3, 2:2:1 and 3:2:1) with three different soil water potential; -20 kPa (high), -60 kPa (medium) and -100 kPa (low). Soil water potential in each growing media was measured by gypsum block.